1998
DOI: 10.1111/j.1600-0773.1998.tb01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Early Carbon Tetrachloride Toxicity in Cultured Rat Hepatocytes

Abstract: CCl, causes liver necrosis in a dose-dependent manner in v i m However, we found that primary rat hepatocytes in culture were killed after a 2 hr incubation with carbon tetrachloride gas at CC14 partial pressures above a threshold between 45 and 54 mmHg. Below this threshold concentration no increase in hepatocyte death was observed. We sought to explain the very abrupt C C 4 concentration threshold for hepatocyte death. Two inhibitors of cytochrome P450 2E1, cimetidine and diallyl sulfide, inhibited lipid per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(75 citation statements)
references
References 39 publications
2
72
0
1
Order By: Relevance
“…The hepatotoxic effects of CCl4 are attributed to its metabolism by P450 to yield toxic trichloromethyl radicals that can act as free radical initiators [28] . These radicals are believed to induce injury either by interacting with the unsaturated fatty acids of cell membranes, thereby causing lipid peroxidation, or by binding covalently to important macromolecules such as proteins, lipids, or DNA [29,30] .…”
Section: Resultsmentioning
confidence: 99%
“…The hepatotoxic effects of CCl4 are attributed to its metabolism by P450 to yield toxic trichloromethyl radicals that can act as free radical initiators [28] . These radicals are believed to induce injury either by interacting with the unsaturated fatty acids of cell membranes, thereby causing lipid peroxidation, or by binding covalently to important macromolecules such as proteins, lipids, or DNA [29,30] .…”
Section: Resultsmentioning
confidence: 99%
“…The hepatotoxic effects of CCl 4 are largely due to its active metabolite, trichloromethyl radical [16]. These activated radicals bind covalently to the macromolecules and induce peroxidative degradation of membrane lipids of endoplasmic reticulum rich in polyunsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Johnston and Kroening (1998) have observed that CIM inhibited LP in primary rats hepatocytes in culture but it did not reduce hepatocyte death induced by CCl 4 . We have found here that CIM alone did not produce any alteration in the LP index.…”
Section: Experimental Therapeuticsmentioning
confidence: 89%